Epidemiological Study of COVID-19 in Iran and the World: A Review Study - Ansari, Nasges; Shokri, Samira; Pirhadi, Mohadeseh; Abbaszadeh, Saber; Manouchehri, Aliasghar (Infectious Disorders - Drug Targets, 2022)
COVID-19 is a new virus of the Coronaviridae family that is now spreading worldwide. Therefore, disseminating information about patients with the virus can help identify the virus, pathogenesis, and find treatments. The current study aimed to review the new coronavirus (COVID-19). To reach this aim, we searched keywords containing COVID-19, coronavirus, respiratory infection, epidemiology in Pub Med, Web of Science Direct, Scopus, Scientific Information Databases, and Google scholar. The results of our search led to the achievement of articles on the study of COVID-19. Based on the results of the study, COVID-19 is a global transmitter with rapid transmission power for which no specific drug has yet been found to treat it. The rapid spread of the COVID-19 virus, the relationship between disease severity and mortality with various factors, respiratory transmission, especially in the short distance, masks, hand washing, and physical distance observance as the most important way to prevent, diversify clinical symptoms and at the same time fever and cough as the most common clinical symptoms, treatment with non-specific antiviral drugs and treatment based on controlling clinical symptoms and strengthening immunity with known drugs, paying attention to children as asymptomatic carriers, and pretentious pregnancy in the event of COVID-19 are the most important findings of this study. The case fatality rate of COVID-19 has varied from 0.08% to 10.8% in the world, but fortunately, the number of patients who have recovered is very promising and more than 66 million people have recovered. There is still no effective drug or vaccine to prevent the disease and investigation in this field is ongoing. The only way to prevent and control the disease is adherence to the health protocols. Due to the need of the medical community to achieve the scientific results of this epidemic in Iran and other parts of the world, this article was written.
Keywords: epidemiology